"Every Evil Pales in Comparison to Thomas's Wickedness": The Physical Punishments and Torture Inflicted by Thomas Preljubović, According to the Author of the Chronicle of Ioannina - Radić, Radivoj Đ.; Vasić, Dejana (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2025)
Chronicle of Ioannina is a 15th-century prose chronicle and represents the longest and most comprehensive preserved text about medieval Epirus. This source describes the tyrannical rule of Thomas Preljubović in Ioannina (1366/7–1384). According to the author of the Chronicle of Ioannina, Thomas Preljubović's governance in this city is depicted as a time of fear and terror. The chronicler portrays numerous hardships and abuses suffered by the inhabitants of Ioannina with undisguised bitterness, often repeating the phrase, "Every evil pales in comparison to Thomas's wickedness" thereby emphasizing the scale of the terror sown by Thomas Preljubović during his reign of terror, which lasted from 1366/1367 to 1384. Among the many atrocities attributed to Thomas Preljubović, the chronicler most frequently mentions imprisonment, enslavement, executions, as well as blinding, mutilation, hanging, quartering by horses, water torture, and other forms of punishment characteristic of the medieval period.
Keywords: Torture; Corporal Punishment; Chronicle of Ioannina; Thomas Preljubović